Answer:
k = - 6
Step-by-step explanation:
Since (x - 2) is a factor then x = 2 is a root
Substitute x = 2 into the polynomial and equate to zero, that is
2³ + k(2)² + 12(2) - 8 = 0
8 + 4k + 24 - 8 = 0
4k + 24 = 0 ( subtract 24 from both sides )
4k = - 24 ( divide both sides by 4 )
k = - 6
Answer:
540
Step-by-step explanation:
3% of 6000 is 180. Multiply that by 3 years and you have your result.
1/3 of 2/3
Just multiply them
1/3 x 2/3 = 2/9
7x+3+5x²
ax²+bx+c
5x²+7x+3
Hoped this helped!
Answer:
5
Step-by-step explanation:
because 5•5=25 and 25-13=12